“YOU AND I DO NOT ‘SHARE’ THE SAME CONSCIOUSNESS”: APPLYING A NOMINALIST BUDDHIST SEMANTIC PERSPECTIVE TO THE GENERAL EXPRESSION “CONSCIOUSNESS” - Paulo Júnio de Oliveira (Kínesis)
It is recognized that Buddhadharma schools are markedly ontologically, epistemologically, and semantically nominalist. Regardless of that, when it comes to the use of the term “consciousness”, there is still a tendency in some Western circles to understand Buddhism in a solipsist or monist way. To this purpose, I argue that the general expression “consciousness” from Buddhadharma texts must be understood according to traditional nominalist Buddhist semantics and theory of entities. In the end, I briefly mention some arguments and viewpoints – defending the plurality/diversity of consciousness – of some Buddhist Dzogchen scholars and masters.